Skin barrier in atopic dermatitis: beyond filaggrin - Mariana Colombini Zaniboni; Luciana Paula Samorano; Raquel Leão Orfali; Valéria Aoki (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Atopic dermatitis is a chronic inflammatory skin disease with a complex pathogenesis, where changes in skin barrier and imbalance of the immune system are relevant factors. The skin forms a mechanic and immune barrier, regulating water loss from the internal to the external environment, and protecting the individual from external aggressions, such as microorganisms, ultraviolet radiation and physical trauma. Main components of the skin barrier are located in the outer layers of the epidermis (such as filaggrin), the proteins that form the tight junction (TJ) and components of the innate immune system. Recent data involving skin barrier reveal new information regarding its structure and its role in the mechanic-immunological defense; atopic dermatitis (AD) is an example of a disease related to dysfunctions associated with this complex.